2011
DOI: 10.1542/peds.2010-2796
|View full text |Cite
|
Sign up to set email alerts
|

Care Models and Associated Outcomes in Congenital Heart Surgery

Abstract: We were not able to detect a difference in postoperative morbidity or mortality associated with the presence of a dedicated CICU for children undergoing heart surgery. There may be a survival benefit in certain subgroups .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 37 publications
1
55
0
1
Order By: Relevance
“…Further study is needed to develop and refine a failure to rescue measure in the pediatric cardiac surgery population, to analyze which postoperative complications should be included in such a measure, and to evaluate potential factors that may influence this measure, including differences in training and availability of personnel, and hospital structure, processes, and management practices. 25,26 …”
Section: Discussionmentioning
confidence: 99%
“…Further study is needed to develop and refine a failure to rescue measure in the pediatric cardiac surgery population, to analyze which postoperative complications should be included in such a measure, and to evaluate potential factors that may influence this measure, including differences in training and availability of personnel, and hospital structure, processes, and management practices. 25,26 …”
Section: Discussionmentioning
confidence: 99%
“…Future studies should attempt to better characterize these apparently important, but as yet obscure, factors. One approach would be to assess the relative contributions to LOH of potentially modifiable factors previously reported in focused studies, such as presence of dedicated cardiac intensive care unit [22], use of fast-track protocols to extubation [23] or intensive care discharge [24], and specific approaches to central line care [25], sternal closure [26], and various aspects of blood transfusion management [27]. …”
Section: Discussionmentioning
confidence: 99%
“…However, our study demonstrated that the presence of a dedicated cardiac ICU was associated with lower mortality. In a recent study, Burstein and coworkers [13] did not detect a difference in postoperative morbidity or mortality associated with the presence of a dedicated cardiac ICU for children undergoing cardiac operations.…”
Section: Commentmentioning
confidence: 91%